Perspectives on womanhood in rural America: A qualitative exploration of female identity within a Christian and republican context - Ekblom,Jonna (2023)
Equality between men and women in American society has been an ongoing struggle and debate for centuries. In some ways, the societal position of women has improved, e.g., in terms of gaining access to the labor market. Yet, despite significant changes regarding gender roles and norms, along with an increased necessity of double-income households, old ideals of gender roles and family structures still linger, particularly amongst more conservative parts of the population. The purpose of this investigation was to explore how conceptions of gender roles, both traditional and modern, are produced and negotiated by women, and to examine the connection between notions of femininity and womanhood, and the economic, sociopolitical, and religious context of the women’s geographical locations. For this, a qualitative method has been used, in which five semi-structured interviews were conducted with Caucasian, American women in the ages 46-63 who resided in predominantly republican areas which have a high concentration of white, Christian identity. The results demonstrate a rather traditional view of womanhood, with value being placed on the woman’s role as a mother, in conjunction with the perspective that men and women enjoy equal opportunities in today’s society. Furthermore, the results pointed to an overlap between egalitarian and conservative values amongst the participants and displays of conflict between reality and ideals were in some cases found.
Keywords: gender roles; womanhood; motherhood; feminism; conservatism; religion; modern and traditional women.